Musharakah Mutanaqisah home financing: a review of literatures and practices of Islamic banks in Malaysia - Osmani, Noor Mohammad; Abdullah, Md. Faruk (World Business Institute, 2010)
This paper analyzes the practice of Islamic Banks in Malaysia in home financing. While conventional banks deal with interest in financing home, car or other appliances, the Islamic banks limit to transactions that are free from interest, usury, ambiguity, cheating etc. Islamic Banks in Malaysia implement certain well-known systems in home financing. The most popular ones are Bay` bi Thaman ‘Aajil (BBA), which is sale on a deferred payment; and Musharakah Mutanaqisah (MM), which means, diminishing partnership. The paper would deal specifically on this MM home financing as it is implemented in Malaysian Islamic banking systems, while drawing a clear line of distinctions between well-known BBA and less practiced MM. It would survey the existing literatures on Islamic Banks in Malaysia and also their practices to reach conclusions on such transactions. Many Islamic banks today accept MM home financing as an alternative to BBA or Murabaha sale, which was in existence since the inception of Islamic Banks in Malaysia. The paper would look into MM from Jurisprudential point of view to see if it could be adopted as it is practiced today, or needs some modifications. It will highlight the characteristics of MM and related issues like ownership and liabilities, shares and ownership transfer, Ijarah and rentals etc. The paper expects to draw certain principles governing the implementation of MM in Islamic home financing to keep it free from interest and making it vibrant and relevant to the financial markets.